Clinical Importance, Incidence and Risk Factors for the Development of Postoperative Ileus Following Adult Spinal Deformity Surgery. Issue 6 (July 2022) - Ohba, Tetsuro; Koyama, Kensuke; Oba, Hiroki; Oda, Kotaro; Tanaka, Nobuki; Haro, Hirotaka
Study Design: Retrospective observational study of a cohort of consecutive patients. Objectives: Postoperative ileus (POI) is associated with a variety of adverse effects. Although the incidence of and risk factors for POI following spinal surgery have been reported, the frequency and pathology of POI after spinal corrective surgery for adult spinal deformity (ASD) are still largely unknown. The study objectives were to: (1) clarify the prevalence and clinical significance of POI, (2) elucidate the risk factors for POI, (3) determine radiographically which preoperative and/or postoperative spinal parameters predominantly influence the risk of POI after spinal corrective surgery for ASD. Methods: We included data from 144 consecutive patients who underwent spinal corrective surgery. Perioperative medical complications and clinical information were extracted from patient electronic medical records. Preoperative radiographic parameters and changes in radiographic parameters after surgery were compared between patients with and without POI. Multivariate logistic regression analyses were performed to clarify potential risk factors for POI. Results: POI developed in 25/144 (17.4%) patients and was the most common complication in the present study. The frequencies of smoking, gastroesophageal reflux disease, and lateral lumbar interbody fusion (LLIF), as well as the duration of surgery were significantly greater in the group with POI versus the group without POI. Among radiographic parameters, only the change in thoracolumbar kyphosis (TLK) from before to after surgery was significantly larger in the group with POI. Multivariate logistic regression analysis showed that male sex, LLIF and large changes in TLK from before to after surgery were significantly associated with the development of POI. Conclusions: These results suggested that LLIF and large corrections in TLK were independent risk factors for POI after ASD surgery. When patients with ASD have large TLK preoperatively, and it is determined that a large correction is needed, physicians must be aware of the potential for occurrence of POI.